Effects of Surface Diffuseness and Coupling Radius Parameters on The Fusion and Quasi-Elastic Barrier Distributions - Viska Inda Variani; Ida Usman; Muhammad Zamrun Firihu (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2019)
We study the heavy-ion reaction at sub-barrier energies for 16O+144,154Smsystems using full order coupled-channels formalism. We especially investigate the effect of fusion and quasi- elastic barrier distributions on the surface diffuseness and the coupling radius parameters of the nuclear potential for these systems. We found that the structure of fusion and quasi-elastic barrier distributions is more sensitive to the surface diffuseness and coupling radius parameters for the reaction with spherical target, 16O+144Sm systemcompared to the reaction that involves the deformed target, i.e., 16O+154Sm system. In more detail, the results of coupled-channels calculations for the fusion and the quasi-elastic barrier distributions for deformed target are not sensitive to the choice of the coupling radius and surface diffuseness parameters. In mark contrast, the structure of the fusion and the quasi-elastic barrier distributions for spherical target are very sensitive to the coupling radius and surface diffuseness parameters. We found that the small surface diffuseness parameter smeared out the fusion barrier distributions and the larger coupling radius smoothed the high energy peak of the quasi-elastic barrier distributions. We also found that the larger coupling radius, , is required by the experimental quasi-elastic barrier distribution for the 16O+144Sm system whereas the experimental fusion barrier distribution compulsory the small value, i.e., .